Pemberdayaan wanita Kelompok Serba Usaha Srikandi melalui diversifikasi produk kopi bubuk herbal - Maria Erna Kustyawati; Ribut Sugiharto; Sri Waluyo; Erlina Erlina (Riau Journal of Empowerment, 2019)
The community service was aimed to improve the quality and enhance the marketing of ground coffee owned by Business Group of Srikandi (KSU Srikandi), a group of women coffee farmers located in Sidorejo, Pekon Ngarip, Ulu Belu Subdistrict, Tanggamus Regency of Lampung. KSU Srikandi has produced ground coffee since 2015. However, the group has problems on limited market and low quality of coffee beans. The community services have been done to overcome the issues. The actions are counselling, demonstrations on constructing production house to enhance the sanitizing program, labelling system, and achieving household industrial food production certificate (P-IRT). The result indicated that the production increase 19.1% in a month due to the labelling system, achievement of P-IRT, and construction of production house, which enhanced sanitizing, staff coordination, and direct product selling. Also, product development of ground coffee with cinnamon aroma helped to expand the market. In the future, KSU Srikandi hopes to make the coffee plantation area and its ground coffee products become a tourism coffee spot.